#TITLE_ALTERNATIVE# - MULIADI NASUTION (NIM : 12212076), BAGUS
Hydraulic fracturing has been applied for years as a method used to release shale gas that stored in abundant reserves in very low permeability rock. In the hydraulic fracturing it is desirable to achieve success in operation due to high cost and time consume. From all the aspects that affects success in its operation, fracturing fluid plays the most crucial roles. This fluid creates adequate fracture width to hold proppant within it, carrying the proppant from the wellbore to the fracture, generating a desired net pressure to control height growth and providing fluid loss control. The fluid is chosen based on some parameters such as safety, environmental concern, non-damaging effect, easiness to mix, cost, compatibility with reservoir rock, and capability to control fluid loss. This thesis focuses on selection of fracturing fluid for application in Indonesian shale gas reservoir. First the based fluid is chosen based on some parameters above as well as its additives. Then using fracturing simulation software FracCade 5.1, the selected fluid is simulated with P3D model is used to model fracture propagation. The well data is obtained from Indonesian shale gas well to represent the characteristic of real shale gas reservoir in Indonesia. This simulation is conducted to examine each fluid performance to achieve best in purpose. It is expected from the discussion in this thesis for advance research in fracturing fluid that is applicable for Indonesian shale reservoir.